Navigating the Infodemic: A Bibliometric Analysis of Media Literacy Research in the Social Media Landscape - Crisha Mae E. Villaruel; Joanna Marie V. Gregorio; Nomer Kirby S. Bonifacio; Gladilyn G. Dulay; Jennifer P. Solis (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
The rapid growth of digital platforms has contributed to the faster spread of misinformation. As a result, the researchers become increasingly interested in media literacy as a way to help people understand and respond to the information they encounter online. This research paper provides a detailed bibliometric overview of global research on media literacy and misinformation published between the year 2016 and 2025. Using a Scopus dataset with 18,035 entries, data were cleaned and filtered using RStudio and Bibliometrix resulting to 856 records. The tools Biblioshiny and Vosviewer were used in investigating the published trends, influential sources and authors, citation patterns, and subjects structure. The findings showed a large increase in research output, especially after 2020, It indicates increased public concern during the COVID-19 pandemic. Annual scientific production has also greatly increased, reaching its peak in 2025, showing that researchers are continuing to prioritize media literacy as an important in contemporary age. Citation patterns show that during earlier publications, especially those published between 2017 and 2020, remains important and extremely influential and has serving as a foundation for future research. Leading publications like the Journal of Media Literacy Education and Media and Communication became an important publishing outlet, while a small group of highly influential authors have shaped what most researchers focuses on and discuss in the field, influencing the direction of future research and helping to build the ongoing discussion in media literacy academically.